Physical Simulation on Molten Steel Flow Characteristics of RH Vacuum Chamber with Arched Snorkels - Zhi-Feng Ren; Zhi-Guo Luo; Fan-Xia Meng; Zong-Shu Zou; Yi-Hong Li; Ai-Chun Zhao; Hai-Lian Gui (Advances in Materials Science and Engineering, 2020)
The RH vacuum refining technology is a vitally powerful method of producing clean steel. The inner diameter of traditional circular snorkel is very difficult to be increased owing to the metallurgical refractory thickness around the snorkels and the limitation of the area under the vacuum chamber, limiting the increase in refining efficiency. In order to improve the refining efficiency of the RH reactor, a new designed RH degasser with an optimized arched snorkel is established. This design replaces the traditional two circular snorkels structure with the two arched snorkels and greatly enhances the cross-sectional area of snorkel. In this study, the flow characteristics of this new type RH were studied and analyzed by establishing a 1 : 5.5 physical model of RH with arched snorkels. Results show that the circulation flow rate of RH with arched snorkels can increase by 100% ∼ 180% and the mixing time approximately decreases by 35% compared with RH with circular snorkels under actual production conditions. The circulation flow rate of RH with arched snorkels continues to increase obviously when gas flow rate exceeds the saturated value of RH with circular snorkels. The RH with arched snorkels can increase the refining efficiency significantly and has important application prospect.